3(2)-11=2(2-2)-5

Simple and best practice solution for 3(2)-11=2(2-2)-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2)-11=2(2-2)-5 equation:


Simplifying
3(2) + -11 = 2(2 + -2) + -5

Multiply 3 * 2
6 + -11 = 2(2 + -2) + -5

Combine like terms: 6 + -11 = -5
-5 = 2(2 + -2) + -5

Combine like terms: 2 + -2 = 0
-5 = 2(0) + -5

Multiply 2 * 0
-5 = 0 + -5

Anything times zero is zero.
-5 = 0 + -5

Combine like terms: 0 + -5 = -5
-5 = -5

Add '5' to each side of the equation.
-5 + 5 = -5 + 5

Combine like terms: -5 + 5 = 0
0 = -5 + 5

Combine like terms: -5 + 5 = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 16=3(2b-4)-2b | | -3(2x+4)+1=-11-6x | | 2(4-3x)=82-2x | | 4(.75x+4)-3x=5 | | x^2-2=-8x | | 4x-7+6x=23 | | 7/10•1/3 | | -2(3n+4)=(-6n-6) | | y=.11x-11+99 | | 11(w-7/2)^2-20=101 | | -3x+10=-5(x+7)-9 | | 14/3*5/11 | | 4x^2+61=28x | | F(x)=xsquared-8x+13 | | -5x+2=-53 | | 0.4(m-48)=1.2m | | 7/10*1/3 | | 3p+5=3p-5 | | y=.11(x-100)+99 | | 4a+31=7a+10 | | 2y-8=-3y+-6+8 | | y=.10x+175 | | x^2+100=-16x | | X(x+6)=520 | | 7/10•1/3•5/11 | | 5y-2+2y=4 | | 5n-13=2n+8 | | 7/10*1/3*5/11 | | .5(2-7y)+3.5y=1 | | (sinx-5)=0 | | 7w/5=35 | | 9(8d)-5+13=12d-2 |

Equations solver categories